Εικόνα και λόγος: η προβληματική της σχέσης εικόνας και λόγου από τη σκοπιά του Hans-Georg Gadamer και Paul Klee - (:unkn) unknown (My University, 2018)
Though better know as a painter, Paul Klee’s copious writings reflect some of the most revolutionary stands on the topic of the relation between word and image. His work holds a rather unique place among the philosophers of the previous century, and that is because in his work are detected some of the most fundamental problematics concerning the philosophy of art, and especially that of modern art. Taking into account the indisputable impact of logos in the process of philosophy and the capacity of theoretical reflection in Paul Klee’s work, one easily is confronted with the relation between word and image. In the following essay the origin of the problematic is traced historically, through Kant, Hegel and Nietsche, reaching in to Hans-Georg Gadamer. After anatomizing his thesis on the topic, I point out the solution proposed by Gadamer, that of a “new language” to talk about the work of art, free of any prejudices concerning the representational physis of art. Following Paul Klee’s relation with language in general, his thoughts and studies on the relation between his painterly works and logos are pointed out, disproving the superiority of logos over the image, through the temporality of both.
Image and logos: the problematic of the relation between image and logos according to Hans-Georg Gadamer and Paul Klee
Keywords: μοντέρνα τέχνη, εικόνα, λόγος, γλώσσα, Κλεέ, Γκαντάμερ; modern art, image, logos, language, Klee, Gadamer